Cytomegalovirus viral interleukin‐10 in patients with Aspergillus infection and effects on clinical outcome. Issue 7 (31st May 2022) - Huang, Shiang‐Fen; Huang, Yu‐Chi; Lee, Chen‐Te; Chou, Kun‐Ta; Chen, Hsin‐Pai; Huang, Chia‐Chang; Ji, Dar‐Der; Chan, Yu‐Jiun; Yang, Ying‐Ying
Abstract: Background: Human cytomegalovirus (CMV) is associated with aspergillosis, but the simultaneous presence of CMV viral interleukin‐10 (cmvIL‐10) and aspergillosis has never been investigated. CmvIL‐10 is produced by CMV‐infected cells and acts as an immune modulator during CMV infection. The aim of this study was to evaluate cmvIL‐10 levels in peripheral blood and its influence on the clinical outcomes of Aspergillus infection. Methods: Patients who visited or were admitted to the hospital with suspected Aspergillus infection, including invasive aspergillosis (IA) and chronic pulmonary aspergillosis (CPA), were prospectively enrolled. The cmvIL‐10, human IL‐10 (hIL‐10), IL‐1B, IL‐6, IL‐8, IFN‐γ, and TNF‐α levels in peripheral blood were measured. Results: Patients with Aspergillus infection had a higher level of cmvIL‐10 than the control group (158 ± 305 vs 27.9 ± 30.4 pg/ml, p < .05). The level of cmvIL‐10 was not correlated with CMV viremia or end‐organ disease. The cmvIL‐10 but not hIL‐10 level was positively correlated with the IFN‐γ level ( p < .05) and marginally negatively correlated with IL‐1B and IL‐8 levels ( p < .1). In patients with CPA, a high level of cmvIL‐10 (≥100 pg/ml) was a poor prognostic factor for long‐term survival ( p < .05). In contrast, CMV viremia or end‐organ disease was associated with poor survival in patients with IA ( p = .05). Conclusions: Aspergillus infection was associated with CMV coinfection with cmvIL‐10 in blood. A cmvIL‐10 concentration ≥100 pg/ml was a predictor for unfavourable outcome in CPA patients.